The use of comic book as a media in teaching reading comprehension to improve students' vocabulary mastery - Desi Purnama Sari; Sofyan Abdul Gani; Saiful Marhaban (Universitas Syiah Kuala, 2021)
Improving vocabulary mastery of students requires creativity in finding some strategies in order that students are motivated to memorize the vocabulary. This research aimed to use a comic book to improve student's vocabulary mastery through reading comprehension. The researcher focused on the use of Snow White comic book in improving students’ vocabulary mastery. The data were collected by doing tests. The tests were divided into pre-test and post-test to see the students’ ability on their vocabulary mastery before and after the treatment, and a questionnaire was used to see the students’ responses toward the approach. The samples are the students of MAN 2 Montasik Aceh Besar, consisted of 40 students who were divided into experimental class and control class. The obtained data were analyzed using descriptive statistics through SPSS Version 22. The result of the hypothesis testing of this research showed that students’ vocabulary mastery was significantly improved. The students’ responses toward the use of comic book to improve their vocabulary mastery were positive and the students showed their interest in reading. Therefore, the use of comic book to improve student's vocabulary mastery through reading comprehension is suggested to be used by teachers to help students in learning and memorizing vocabulary.